Neoadjuvant immunoradiotherapy results in high rate of complete pathological response and clinical to pathological downstaging in locally advanced head and neck squamous cell carcinoma. Issue 5 (7th May 2021) - Leidner, Rom; Crittenden, Marka; Young, Kristina; Xiao, Hong; Wu, Yaping; Couey, Marcus A; Patel, Ashish A; Cheng, Allen C; Watters, Amber L; Bifulco, Carlo; Morris, George; Rushforth, Lessli; et al.
Abstract : Background: Checkpoint inhibitors targeting programmed death receptor-1 (PD-1) have been tested in the neoadjuvant setting for the treatment of locoregionally advanced head and neck squamous cell carcinoma (HNSCC); however, response rates are modest. We hypothesized that adding stereotactic body radiation therapy (SBRT) to anti-PD-1 would be safe prior to definitive surgical resection and would enhance pathological response compared with historical cohorts of patients with locoregionally advanced HNSCC treated with checkpoint inhibitor alone. Methods: The Neoadjuvant Immuno-Radiotherapy Trial was an investigator-initiated single institution phase Ib clinical trial that enrolled patients with previously untreated locally advanced HPV-positive and HPV-negative HNSCC between 2018 and 2019. Eligible patients were treated with neoadjuvant SBRT at a total dose of either 40 Gy in 5 fractions or 24 Gy in 3 fractions, delivered in a 1-week timespan, with or without nivolumab, prior to definitive surgical resection. Patients were then planned for treatment with adjuvant nivolumab for 3 months. The primary safety endpoint was unplanned delay in surgery considered to be at least possibly related to neoadjuvant treatment. The primary efficacy endpoints included pathological complete response (pCR), major pathological response (mPR), and the rate of clinical to pathological downstaging after neoadjuvant treatment. Results: Twenty-one patients underwent neoadjuvant treatment, which was well tolerated and did not delay surgery, thus meeting the primary endpoint. Tissue responses were characterized by robust inflammatory infiltrates in the regression bed, plasma cells and cholesterol clefts. Among the entire study group, the mPR and pCR rate was 86% and 67%, respectively. Clinical to pathological downstaging occurred in 90% of the patients treated. Conclusion: These data demonstrate that radiation delivered only to the gross tumor volume combined with immunotherapy was safe, resulted in a high rate of mPR and should be further evaluated as a locally focused neoadjuvant therapy for patients with head and neck cancer. Trial registration number: This study is registered with clinicaltrials.gov (NCT03247712 ) and is active, but closed to patient accrual.